Evaluation of Biomass Production and Sugar Content of Samurai 2 Variety of Sorghum at Different Cutting Ages and Urea Fertilizer Applications - Harahap, Anwar Efendi; Ali, Arsyadi; Harianti, Fitri (Fakultas Peternakan, Universitas Padjadjaran, 2026)
Sorghum bicolor var Samurai 2 is a well growing variety in dry land. The purpose of this study was to investigate the best total forage biomass production and sugar content in stems as results of different cutting age and urea doses at primary cut and cutting after first and second ratoon. The study used a factorial randomized block design (3 x 3) with 4 replications. The first factor was different age consisting of 80, 85, and 90 days and the second factor was different doses of urea consisting of 200, 300, and 400 kg ha-1. The results showed that there was no significant interaction effect on parameters. At the primary harvest, both cutting age and nitrogen level showed no significant effect (p >0.05) on chlorophyl (unit), panicle proportion (%), and total forage biomass production (ton/ha-1). The cutting age of plant affected (p <0.05) tiller number, the proportion of stem and leaf (%). At second harvest (ratoon 1) there was significant effect of the cutting age (p <0.05) on tiller number, proportion of fresh leaf and total forage biomass production. Furthermore, at third harvest (ratoon 2) the cutting age showed significant effect (p <0.05) on tiller number and leaf proportion. It was found at third harvest (second ratoon) that delaying the cutting age resulted in a significant decrease in total biomass production and an increase in stem brix sugar content (%) compared to first harvest (primary) and second harvest (ratoon 1) in sorghum var Samurai 2